FAKTOR MINAT DAN PERAN PERKEMBANGAN SUKUK TERHADAP PEMBANGUNAN - Chandra Satria; Suandi Suandi (Sekolah Tinggi Ekonomi dan Bisnis Syariah (STEBIS) Indo Global Mandiri Palembang, 2020)
In the period between 2010 and the end of 2018, sharia products, especially sukuk in the Indonesian capital market, have shown quite good development. Total funds under management of sharia mutual funds, or better known as the Net Asset Value (NAV), are recorded at Rp 34.5 trillion. This figure is up by 21.8% compared to 2017. The NAV reflects 6.82% of the total conventional and sharia mutual fund NAV. While the number of Islamic mutual funds that have been circulating in the public, there were 224 mutual funds. This figure increased by 23.1% compared to 2017. The number also reflects 10.7% of the total conventional and sharia mutual funds that have been circulating in public (OJK data sources for 2017 and 2018). In that period, the issuance of sukuk was conducted 104 times by 22 issuers and / or public companies with a total sukuk issuance value of Rp 22 trillion or equivalent to 10.5% of the total bond issuance value. The still low total sukuk issuance value compared to the total bond issuance value shows that there are other factors that influence Issuers / PP's interest in issuing sukuk in addition to regulatory factors related to Islamic capital markets which have had a positive influence on the development of Islamic capital markets, especially sukuk